E-LEARNING: CASE STUDIES IN WEB-CONTROLLED DEVICES AND REMOTE MANIPULATION - Sobh, Tarek; Mihali, Raul; Batra, Puneet; Singh, Amit; Pathak, Sudip; Vitulskis, Tomas; Rosca, Andrew (International Journal of Computing, 2014)
Chances are that distance learning will transparently extend colleges and institutes of education and could plausibly overtake and turn into a preferred choice of higher education, especially for adult and working students. The main idea in e-learning is to build adequate solutions that can assure educational training over the Internet, without requiring a personal presence at the degree offering institution. The advantages are immediate and of unique importance, to enumerate a few: Education costs can be reduced dramatically, both from a student's perspective and the institution's (no need for room and board, for example); The tedious immigration and naturalization issues common with international students are eliminated; The limited campus facilities, faculty members and course schedules an institution can offer are no longer a boundary; Working adults can consider upgrading skills without changing their lifestyles. We are presenting through this material a sequence of projects developed at University of Bridgeport and than can serve well in distance learning education ranging from simple "hobby" style training to professional guidance material. The projects have an engineering / laboratory flavor and are being presented in an arbitrary order, topics ranging from vision and sensing to engineering design, scheduling, remote control and operation.